How do hospital characteristics and ties relate to the uptake of second-generation biosimilars? A longitudinal analysis of Portuguese NHS hospitals, 2015–2021. (2nd January 2023) - Perelman, Julian; Duarte-Ramos, Filipa; Melo Gouveia, António; Pinheiro, Luis; Ramos, Francisco; Vogler, Sabine; Mateus, Céu
ABSTRACT: Background: There is limited evidence on within-country discrepancies in biosimilar uptake. This study analyzes differences in timing and diffusion of biosimilar uptake across Portuguese NHS hospitals and explores possible determinants. Research design and methods: We analyzed publicly accessible consumption data of originator biologic and biosimilar drugs for adalimumab, etanercept, infliximab, rituximab, and trastuzumab, by hospital and month for the years 2015–2021 ( N = 9, 467). We modeled the time to biosimilar adoption using survival regression models and the share of biosimilar consumption using generalized estimated equations with random hospital effects. Results: Academic hospitals were characterized by a quicker uptake of adalimumab and infliximab biosimilars but lower shares for other drugs. A higher total consumption of biologics was related to a lower share of biosimilar uptake. A stronger participation in randomized controlled trials was linked to higher biosimilar shares and quicker uptake, except for rituximab. If all NHS hospitals had biosimilar shares equal to the highest ones, potential annual savings could reach 13.9 million euros. Conclusion: The findings suggest a need for capacity-building on biosimilar prescribing, including for doctors of academic hospitals and those working in settings where high biosimilar use would be expected.